2022
DOI: 10.3390/agriculture12060861
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experiment of Full-Tray Grafting Device for Grafted Melon Seedling Production

Abstract: At present, the existing vegetable grafting machines are cutting and grafting operations for a single plant or row. They need to manually or automatically grab the seedlings, and their grafting efficiency is not significantly higher than that of manual grafting techniques. In this paper, grafted melon seedlings were the subject of the research. Based on the splice-grafting method, we designed a clamping and positioning device for full-tray seedlings and a mechanical device to realize full-tray grafting by loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The results of the study showed that the improved method of producing seedlings from cuttings could increase the survival rate of pumpkins to 98%. Fu et al [41] also found that the current vegetable cutting method or single-bead cutting method is used to produce seedlings, which requires a lot of time and manual seedling grasping. This method of cutting technology has low efficiency rates.…”
Section: Related Workmentioning
confidence: 99%
“…The results of the study showed that the improved method of producing seedlings from cuttings could increase the survival rate of pumpkins to 98%. Fu et al [41] also found that the current vegetable cutting method or single-bead cutting method is used to produce seedlings, which requires a lot of time and manual seedling grasping. This method of cutting technology has low efficiency rates.…”
Section: Related Workmentioning
confidence: 99%
“…However, the high cost of these robots, the strict requirements for the agronomic traits of the scion and rootstock seedlings, and the complexity of their repairs are obstacles to their adoption in China [26]. China began researching grafting machines in the 1990s [27][28][29]. In 2005, China Agricultural University launched the 2JSZ-600 grafting robot, which used a doublearm bidirectional cutting mechanism.…”
Section: Introductionmentioning
confidence: 99%